Association between office blood pressure, antihypertensive medication use and male sexual dysfunction: a penile Doppler study. (25th November 2020) - Ioakeimidis, N; Rokkas, K; Terentes-Printzios, D; Angelis, A; Dima, I; Gardikioti, V; Sigala, E; Aznaouridis, K; Tousoulis, D; Vlachopoulos, C
Abstract: Background: Arterial hypertension is associated with an almost two-fold increase in the likelihood of having an abnormal penile blood flow. Recent evidence supports the independent of age and blood pressure (BP) level predictive value of severe penile arterial insufficiency for adverse cardiovascular events. Purpose: Aim of this study is to quantify the association between BP level and severity of penile vascular disease and to examine the potential for differences in effect of BP lowering medication use on the associations between BP level and penile vascular damage. Methods: We measured penile peak systolic velocity (PSV) in 356 consecutive men with erectile dysfunction (ED) and without a history of diabetes and cardiovascular disease; The cohort was divided according to office systolic BP (SBP) and diastolic BP in three BP categories: normal (SBP <130 and DBP <85 mmHg, n=117), high normal (130≤SBP<140 or DBP 85≤DBP<90mmHg, n=91), and hypertension (SBP≥140 or DBP≥90mmHg, n=148). 164 (46%) patients of the whole study population were treated with antihypertensive medications. Low PSV values after intracavernous injection of prostanglandin E1 indicate impaired penile blood inflow and severe vasculogenic ED. Results: Figure shows PSV measurements of the three office BP categories subdivided according to use of antihypertensive therapy. Treated and untreated hypertensive patients had similar mean PSV. Interestingly, the mean PSV of men with high normal BP not receiving antihypertensive drugs was significantly higher compared to PSV of men with high normal BP under therapy and significantly lower compared to PSV of normotensive males without therapy (all P<0.05). Among males not receiving antihypertensive medications there was a progressive decrease in PSV values from normal BP, to high normal BP and to hypertension (P=0.01, after adjustment for age), while among males under antihypertension therapy, the three BP categories had similar PSV level (P=0.54 after adjustment for age) (figure). Conclusion: The inverse associations observed between hypertension status and penile arterial insufficiency in men not taking antihypertensive medication were attenuated or disappeared among men reporting antihypertensive medication use reflecting a medication effect or structural effects of longstanding hypertension on the penile vasculature. Funding Acknowledgement: Type of funding source: None